The Role of Counseling Teacher in Overcoming Adolescent Determination in School - Rizkayani, Anggita; Lesmana, Gusman (Lembaga Riset Mutiara Akbar, 2023)
The purpose of this study is to describe and describe the study and concept of the development of juvenile delinquency in the world of education which is addressed by the role of the guidance and counseling teacher (BK) in overcoming the problem. This article was written using references from previous research related to the study of the role of counseling teachers in overcoming the development of juvenile delinquency at school age. The results of this literature review resulted in the conclusion that juvenile delinquency in the school environment can be reduced and minimized by the creativity of the counseling teacher in keeping students busy in activities that are more useful than the behavior of students who are not useful in filling their free time. From that it can be concluded that the role of the counseling teacher must be maximized in schools